Analysing the benefit and effect of physical activity during menopause - Oluwayemisi David, Deborah (Annales kinesiologiae (Koper), 2025)
Purpose: The increasing prevalence of menopause-related discomforts, coupled with the potential for non-pharmacological interventions, underscores the need to explore lifestyle modifications such as physical activity (PA). This study aimed to evaluate the effects of pre-existing PA on the quality of life (QoL) in menopausal women. Method: Conducted between September 2022 and January 2023, the cross-sectional study utilized IBM SPSS Statistics (version 23) and included 138 women. Standardized QoL questionnaires (MENQOL and SF-36) and the Global Physical Activity Questionnaire (GPAQ) to assess their PA levels and QoL outcomes. Result: Among participants, 64% engaged in moderate-intensity PA, averaging 90 minutes per week in recreational activities, while spending 75 minutes per day sedentary. A significant inverse relationship was observed between total PA and menopause-related symptoms, with strong negative correlations in the Psychosocial (r = -0.398, p < 0.001) and Vasomotor (r = -0.284, p < 0.001) domains of MENQOL. Women who met the 150 minutes/week recommendation for moderate-to-vigorous physical activity (MVPA) reported significantly better psychological QoL (p = 0.025) as measured by SF-36. Furthermore, positive associations were noted between work-related PA and general health outcomes, suggesting that PA benefits extend across various health dimensions. Conclusions: These findings highlight the role of PA in improving menopausal QoL and emphasize the importance of incorporating personalized PA recommendations into menopausal care. Further research using objective PA measurements and a larger, more diverse cohort is recommended to confirm these results and provide deeper insights.
Keywords: menopausal symptoms; menopause; menopavza; MENQOL; physical activity; SF-36; simptomi menopavze; telesna dejavnost; women; ženske